Urban-rural disparities of child health and nutritional status in China from 1989 to 2006 - Hong Liu; Hai Fang; Zhong Zhao (Institute for the Study of Labor (IZA), 2012)
This paper analyzes urban-rural disparities of China's child health and nutritional status using the China Health and Nutrition Survey data from 1989 to 2006. We investigate degrees of health and nutritional disparities between urban and rural children in China as well as how such disparities have changed during the period 1989-2006. The results show that on average urban children have 0.29 higher height-for-age z-scores and 0.19 greater weight-for-age z-scores than rural children. Urban children are approximately 40% less likely to be stunted (OR = 0.62; P < 0.01) or underweight (OR = 0.62; P < 0.05) during the period 1989-2006. We also find that the urban-rural health and nutritional disparities have been declining significantly from 1989 to 2006. Both urban and rural children have increased consumption of high protein and fat foods from 1989 to 2006, but the urban-rural difference decreased over time. Moreover, the urban-rural gap in child preventive health care access was also reduced during this period.
urn:nbn:de:101:1-2012081412543
Keywords: I14; I15; 330; child; health and nutritional status; urban-rural disparities; China; Kinder; Gesundheit; Ernährung; Ländlicher Raum; Stadt; Regionale Disparität; China